A secondary research on human endocrine physiology in Al- Qur’an and Hadith - Abdul Ghani, Radiah; Ikmal Hisham, Ahmad Irfan; Ahmad Rosli, Athirah Nur (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Understanding physiology, its purpose and function has a great impact on human understanding of themselves. Despite positive progression on the scientific findings in physiology, it is not reflected with the worldview of Islam, and such system produces individuals with little concern towards remembrance of Allah. Thus, this paper aims to review the relevant scientific knowledge in endocrine physiology and relate with Qur’anic verses and Hadith. The view from Islamic perspective has been elaborated with the role of melatonin and cortisol with the change of the day and night. Moreover, the role touch and the release of oxytocin has been described based on Sunnah by Prophet Muhammad (PBUH). It is suggested that the view of more integration of Islamic perspective with other ‘key’ systems in human physiology such as cardiovascular and digestive system should be elaborated. It is hoped that in future serious effort will be done to integrate the scientific knowledge with Islamic perspective therefore the next generation will be able to feel the oneness and greatness of Allah.